Relationship between Metabolic Syndrome Components and COVID-19 Disease Severity in Hospitalized Patients: A Pilot Study - Hande Erman; Banu Boyuk; Meltem Sertbas; Ali Ozdemir (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Preliminary data suggest that patients with comorbidities are more susceptible to severe COVID-19 infection. However, data regarding the presence of metabolic syndrome (MetS) in patients with COVID-19 are scarce. Aim. In the present study, we aim to investigate the association between MetS components and disease severity in hospitalized COVID-19 patients. Methods. We conducted a prospective observational study of 90 hospitalized patients with COVID-19 pneumonia at a tertiary hospital. The study population consisted of inpatients who tested positive by the reverse transcription polymerase chain reaction (RT-PCR) for SARS-CoV-2. Patients with critical COVID-19 disease on admission were excluded. Adult Treatment Panel III of the National Cholesterol Education Program (NCEP-ATP III) criteria were used to define MetS. Laboratory analysis and thorax CT were performed on admission. Results. 90 patients, 60 moderate and 30 severe COVID-19 patients, included in the study. The percentage of MetS cases was higher among severe COVID-19 patients (p=0.018). Of the MetS criteria fasting blood glucose (p=0.004), triglycerides (p=0.007) were significantly higher in patients with severe COVID-19 disease with no statistical significance found in waist circumference (WC) (p=0.348), systolic blood pressure (p=0.429), and HDL-C levels (p=0.263) between two groups. Body mass index (BMI) values were similar in both severe and moderate cases (p=0.854). In logistic regression analysis, serum triglycerides (p=0.024), HDL-C (p=0.006), and WC (p=0.004) were found as independent prognostic factor for severe COVID-19 infection. Conclusion. Severe COVID-19 patients have higher rates of MetS. Serum triglycerides, HDL-C, and WC have an impact on disease severity in COVID-19.